Treatment Response to Sorafenib in Liver Cancer; A Comprehensive Review on Association with Single Nucleotide Polymorphisms (Precision Medicine Communications, 2024)
Liver cancer is one of the most challenging cancers to diagnose and treat. Sorafenib is a tyrosine kinase inhibitor (TKI) that is prescribed for advanced or unresectable liver cancer. While this drug is one of the already-limited choices for liver cancer treatment, sorafenib resistance and variation in therapeutic response add further to the difficulties in pharmacotherapy for liver cancers. There are various ways in which cancer cells can protect themselves from these drugs; genetic polymorphism is one of the ways through which the mechanisms of varied responses to sorafenib can be comprehended. Notably, studies including genes involved in pharmacokinetics of sorafenib like ATP binding cassette subfamily B member 1 (ABCB1 rs2032582, rs1045642), ATP binding cassette subfamily G member 2 (ABCG2 rs2231137, rs2231142, rs2622604), ATP binding cassette subfamily C member 2 (ABCC2/ MRP2  rs3740066), UDP glucuronosyltransferase family 1 member A1 (UGT1A1  rs8175347), UDP glucuronosyltransferase family 1 member A9 (UGT1A9 rs17868320, rs72551330, rs6714486), Cytochrome p450 system ( CYP3A5*3 rs776746), (CYP3A4 rs2740574), (CYP26A1 rs7905939), Solute carrier organic anion transporter family member 1 B1 (SLCO1B1 rs2306283, rs4149056), Solute carrier family 22 member 14 (SLC22A14 rs149738, rs171248, rs183574), Solute carrier family 15 member 2 (SLC15A2 rs2257212) in addition to genes involved in agiogenesis,  like nitric oxide synthase 3 /endothelial NOS (NOS3/eNOS rs2070744, rs2070744, rs2070744, rs61722009, rs1799983), vascular endothelial growth factor A (VEGF-A rs25648, rs833061, rs699947, rs2010963), vascular endothelial growth factor C (VEGF-C rs4604006, rs664393), kinase insert domain receptor (KDR/VEGFR-2 rs2071559, rs2305948, rs1870377, rs4864950), hypoxia inducible factor 1 subunit alpha (HIF-1A rs1951795, rs10873142, rs12434438, rs12434438), fibroblast growth factor 2 (FGF2 rs308379, rs308447) were analyzed in this article. Some of these SNPs were associated with favorable therapeutic outcomes, while others correlated with chemo-resistance or adverse events (AEs) after sorafenib administration. Some AEs showed counter-intuitive results i.e. association with improved overall survival (OS) and progression-free survival (PFS). This review article exhaustively covers and analyzes the pharmacogenomic mechanisms involved in the variation of sorafenib therapeutic response.
Keywords: Liver cancer; sorafenib; genetic polymorphism; treatment response; adverse effects